Discourse Analysis of Tujaqi Poetry: A Local Wisdom of Gorontalo in Respecting Leaders and Honour Guest - Pateda, Lamsike; Muda, Lisdawati (Al-Lisan: Jurnal Bahasa, 2023)
This study aims to describe the meaning of Tujaqi poetry in the traditional ceremony of receiving leaders or honour guests. The arrangement of words and sentences in Tujaqi is a message conveyed by traditional officials to guests or leaders. Appreciation for leaders or guests is expected that leaders and guests try to maintain behaviour from bad habits and maintain behaviour that is beneficial to other people, especially the people of Gorontalo who have been willing to welcome them kindly. This research used discourse analysis to analyse Tujaqi meaning. The procedures were collecting data, identifying unit analysis, segmenting the text, identifying language elements, analysing the meaning, and interpreting the context. The research showed that Tujaqi poetry was recited in Pohutu Motombulu, a traditional ceremony in welcoming a leader or honour guest.  Tujaqi can be interpreted as the artistic creativity of the Gorontalo people, composed in the regional language which symbolizes that the Gorontalo people are proud of their regional language, and are pleased with their own variety of literature and culture so that they are considered equal to other regions.